Diagnostic Approaches to Moyamoya Disease in a Patient with Head Trauma - Putri, Amanda; Kesuma Ningrum, Mutiara; Rachman Kemal, Mohammad Arief; Gunawan, Kevin (Acta Neurologica Indonesia, 2026)
Introduction: Moyamoya Disease (MMD) is a chronic cerebrovascular disorder characterized by progressive stenosis and occlusion of the distal internal carotid artery and the proximal segments of the middle and anterior cerebral arteries. This leads to the development of abnormal vascular networks at the base of the skull, resulting in a "puff of smoke" appearance, which is a hallmark of the disease1. This condition leads to reduced cerebral blood flow and a heightened risk of stroke. Early diagnosis through imaging techniques like Digital Subtraction Angiography (DSA) is essential for effective management. Case Report: A 27-year-old male presented with decreased consciousness after a traffic accident. He was initially assessed with a Glasgow Coma Scale (GCS) score of E1M2V1 and left-sided hemiparesis. Despite undergoing decompressive craniectomy, the patient developed left-sided hemiplegia one week later, which did not correlate with the initial haemorrhagic pattern on CT. DSA revealed stenosis from the C7 segment to the A1-M1 proximal right ICA, and the case was classified as Suzuki stage IV. Discussion: MMD diagnosis relies on advanced imaging, with DSA being the gold standard for assessing the extent of stenosis and collateral vessel formation. The Suzuki classification system helps determine disease progression and informs treatment decisions. In this case, DSA provided crucial information for diagnosis and management, highlighting the advanced stage of the disease. Conclusion: This case underscores the importance of early diagnosis in Moyamoya disease, particularly using DSA for accurate staging. Timely intervention is critical to reduce stroke risk and improve outcomes, especially in advanced stages.